Qualitative Assessment Of The Social Stigma And Discrimination Faced By Tuberculosis Patients Residing In Ernakulam District, Kerala - Charutha Retnakumar; Leyanna Susan George (International Journal Of Community Service, 2022)
Tuberculosis is one of the chronic infectious diseases which is heavily stigmatized and mostly leads to abandonment, social isolation, and condemnation from society. The study aims to qualitatively analyze the social stigma and discrimination faced by tuberculosis patients residing in the Ernakulam district using the grounded theory approach.A qualitative study was conducted among purposively selected TB patients, family members of TB patients, medical officers, senior treatment supervisors, Senior lab supervisors, and Health visitors. Qualitative data was collected till saturation was obtained. The audio recorded data was then translated, transcribed, and manually coded. Thematic analysis and data source triangulation was carried out and conclusions were made. Self-stigma was found to be more evident among the patients since they feared contempt from society, due to which the majority of the patients hide their TB status from society. The revelation of TB status to family members and at the workplace led to the isolation of a few patients.  However, the friendly interaction of healthcare workers helped to reduce social stigma and discrimination. Stigma & discrimination that persist in the community, have a negative impact on treatment adherence of TB patients and thereby delay TB elimination.